A Nano‐Imaging Study of Graphene Edge Plasmons with Chirality‐Dependent Dispersions. Issue 10 (24th March 2021) - Wang, Ximiao; Zheng, Zebo; Xu, Ningsheng; Wang, Weiliang; Chen, Huanjun; Deng, Shaozhi
Abstract: Graphene plasmons (GPs) have a variety of potential applications in nanophotonics and optoelectronics, such as room temperature mid‐infrared photodetectors, sensors, and modulators, due to their ultrahigh electromagnetic field confinements. In particular, the GPs at the edges of a monolayer graphene have been demonstrated to exhibit superior electromagnetic field confinements compared to the sheet plasmons. The graphene is terminated by two types of edges with different chiralities, that is, zigzag or armchair edge. Here, study of the plasmon modes at these two edges and their dispersions, is reported. The authors manage to visualize these two edges using a nano‐imaging technique, and show that edge plasmon behaviors are strongly dependent on chirality. The plasmon dispersions of these two edges can be modified upon chemical doping. Due to the stronger molecule absorption ability of the zigzag edge, the associated plasmons exhibit a broader tuning range. Abstract : Near‐field optical distributions associated with edge plasmon modes propagating along the graphene zigzag and armchair edges are directly visualized and compared. The results indicate that chirality of the edge can have great impacts on the edge plasmon modes, where the zigzag edge exhibits more significant plasmon wavelength shifts upon chemical doping, making it superior in applications of nanoscale molecular sensing.